(untitled) (Revista Contexto & Saúde, 2026)
Objective: this study’s objective is to identify and describe the knowledge of health secretaries, Primary Care coordinators, and professionals who provide Integrative and Complementary Health Practices regarding the National Policy on Integrative and Complementary Health Practices. Method: this is a qualitative study conducted in the VI Health Region of Rio Grande do Norte, which comprises 37 municipalities. The study included 66 participants divided among health secretaries, coordinators, and health professionals. The instruments used to obtain the results were semi-structured interviews and non-participant observation. The data were analyzed using thematic content analysis. The study was submitted to the ethics committee and approved. Result: knowledge about Integrative and Complementary Health Practices among managers, coordinators, and health professionals is uneven, ranging from a deep understanding to a superficial or incorrect comprehension. Conclusion: lack of knowledge leads to misconceptions that these practices are less scientific or technical, which undermines their credibility and hinders their implementation in health services. Continuing education has strong potential to overcome the lack of knowledge and the challenges related to the provision of integrative and complementary health practices .